Asymmetrical zinc(II) phthalocyanines conjugated to nanomaterials for degradation of organic pollutants and inactivation of Staphylococcus aureus bacteria - Mgidlana, Sithi (Rhodes University, Faculty of Science, Department of Chemistry)
This thesis reports on the syntheses and characterization of asymmetrical phthalocyanines (Pcs) with different ring substituents (tert-butyl, ester, diimide, trimethoxy, acetophenone, heptanoylphenoxy, perfluorophenoxy, dimethoxy, propanoic acid, acetic acid, carboxylic acid, aminophenoxy, acrylic acid). Several nanoparticles including metal tungstate, capped with glutathione and 1-mercaptohexanol are prepared and characterized using analytical techniques. The synthesized Pcs are covalently linked to various nanoparticles (NPs) through ester and amide bonds to form Pc-NP conjugates, in order to improve their catalytic properties. The Pcs and their conjugates are characterized using different analytical techniques. The photophysics and photochemistry of the MPcs and conjugates are studied. The conjugates T). The complexes and the conjugates with nanomaterials are evaluated for singlet oxygen-generating ability. Conjugates generate higher singlet oxygen in comparison to Pc complexes alone. The photocatalytic activity of the conjugates of ZnPc complexes with NiWO4, Ag2WO4, Bi2WO6, CoWO4, and Ag-Fe3O4-based nanoparticles is evaluated based on photodegradation of methylene blue, tetracycline, and dibenzothiophene. The photocatalytic efficiencies of the synthesized phthalocyanine complexes increased in the presence of nanoparticles. This work also reports on the photodynamic antimicrobial chemotherapy activity of these materials against Staphylococcus aureus (S. aureus) bacteria in DMSO. The results indicated that silver-based nanoconjugates exhibit high antimicrobial activity with high log reductions compared to NiWO4, CoWO4, and Ag-Fe3O4-based materials. The z-scan technique is employed to experimentally test the nonlinear optical response of complexes and nanoconjugates in solution. The nonlinear absorption coefficient, third-order optical susceptibility and optical limiting threshold of the materials are obtained from the Z-scan aperture data. The nonlinear absorption parameters improved in the presence of semiconductor quantum dots, with 1-ethanoic-CdTe/ZnSeS/ZnO giving the best results due to the presence of electron-donating substituents.
Keywords: Active oxygen; Tungstates; Nanoparticles; Asymmetry (Chemistry); Zinc phthalocyanine; Photocatalysis; Desulfurization; Photoinhibition; Staphylococcus aureus